Policing "conjugal order": gender, hybridity and vernacular security in Fiji. Issue 1 (2nd January 2017) - George, Nicole
ABSTRACT: This article develops a feminist critique of debate on hybrid forms of governance in global politics by demonstrating the gendered implications (and limitations) of hybridized approaches to security provision. The conceptual approach that frames my enquiry puts arguments advancing the benefits of multilayered and hybridized security into dialogue with ethnographic enquiry on "vernacular" security and feminist study of "conjugal order." I contend that this conceptual approach is particularly productive for examining the gendered policing outcomes that can be produced in environments where vernacular influences – customary and religious – inflect prevailing idioms of security and order. To further defend this claim, I apply this conceptual approach to a case study of gender and policing in Fiji. Although there has been a strong state rhetoric of progressive reform on gender policy in this context, efforts to reform policing have been hamstrung by longstanding customary and religious discourses that emphasize the defense of conjugal norms as foundational to the achievement of order and safety. I show how this scenario has encouraged a practical policing of gender and sexuality that is restrictive for women generally and may expose particular groups of women to direct forms of insecurity and violence.